Penentuan Chemicals Kritis pada Industri Migas Menggunakan Analisis ABC (Studi Kasus pada Petro China Internatioal Jabung Ltd.) - Eka Febriani; Nur Indrianti (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Chemicals are key supporting items for production processes in the oil and gas industry. One of the strategies to control the supply of the chemicals is identifying them based on their critical level. This study deals with the identification of critical chemicals in a private oil and gas company. Currently there are 47 chemicals that are declared by the company as critical items. The company determined critical itemsmainly based on theirdemand. In this study we identified the critical level of the chemicals using ABC analysis. We used the last five-year data and considered the total inventory costs of each item. The study shows different result from the one that is currently done by the company. The analysis indicates that there are 14 chemicals that are classified as critical items. The result of the study can be used as the basis for the company to control the inventory of the critical chemicals. In addition to inventory costs, future study can be done to develop method for classifying critical itemsby taking into accountmultiple criteria such as expired date, ordering lot size, and delivery time of the materials.